UNDERSTANDING THE FRAMEWORK OF THE ANTYODAYA PLAN - Shabir Ahmad Lone; Sarfaraz Ahmad Rather (PT. Radja Intercontinental Publishing, 2024)
Over 50,000 villages across the country have adopted Mission Antyodaya, which has had a significant positive impact on poverty reduction, improved access to key services, and promoted equitable growth. However, the effort faces a number of challenges, including a lack of adequate funding, ineffective monitoring methods, and hostility from well-established power structures. These challenges must be addressed in order for the program to be successful and to ensure that the most marginalised people in society benefit from development.